Depression screening using patient-targeted feedback in general practices: study protocol of the German multicentre GET.FEEDBACK.GP randomised controlled trial. Issue 9 (21st September 2020) - Kohlmann, Sebastian; Lehmann, Marco; Eisele, Marion; Braunschneider, Lea-Elena; Marx, Gabriella; Zapf, Antonia; Wegscheider, Karl; Härter, Martin; König, Hans-Helmut; Gallinat, Jürgen; Joos, Stefanie; Resmark, Gaby; et al.
Abstract : Introduction: Approximately one out of six patients in primary care suffers from depression, which often remains undetected. Evidence regarding the efficacy of depression screening in primary care, however, is inconsistent. A previous single-centre randomised controlled trial (RCT) in cardiac patients, the DEPSCREEN-INFO trial, provided the first evidence that written feedback to patients following a positive depression screening reduces depression severity and leads to more comprehensive patient engagement in mental healthcare. To amplify these effects, the feedback should be tailored according to patients' needs and preferences. The GET.FEEDBACK.GP RCT will test the efficacy of this patient-targeted feedback intervention in primary care. Methods and analysis: The multicentre three-arm GET.FEEDBACK.GP RCT aims to recruit a total of 1074 primary care patients from North, East and South Germany. Patients will be screened for depression using the Patient Health Questionnaire-9 (PHQ-9). In the case of a positive depression screening result (PHQ-9 score ≥10), the participant will be randomised into one of three groups to either receive (a) patient-targeted and general practitioner (GP)-targeted feedback regarding the depression screening results, (b) only GP-targeted feedback or (c) no feedback. Patients will be followed over a period of 12 months. The primary outcome is depression severity (PHQ-9) 6 months after screening. Secondary outcomes include patient engagement in mental healthcare, professional depression care and cost-effectiveness. According to a statistical analysis plan, the primary endpoint of all randomised patients will be analysed regarding the intention-to-treat principle. Ethics and dissemination: The Ethics Committee of the Hamburg Medical Association approved the study. A clinical trial company will ensure data safety, monitoring and supervision. The multicentre GET.FEEDBACK.GP RCT is the first trial in primary care that tests the efficacy of a patient-targeted feedback intervention as an adjunct to depression screening. Its results have the potential to influence future depression guidelines and will be disseminated in scientific as well as patient-friendly language. Trial registration number: NCT03988985 .